Comprehensive analysis of micro and macro-minerals, phytochemicals and proximate composition of Cordia dichotoma G. forst fruits - Ashmita Singh
Plants have long served as a valuable source of bioactive components in traditional ayurvedic remedies for disease prevention. In our research, we explored an underutilized plant species, Cordia dichotoma G. Forst. Our findings revealed that cordia fruits are rich source of dietary carbohydrates (30.06%), dietary fibers (17.6%) and crude proteins (6.67%). The cordia fruits found in substantial amount of macro-minerals namely K (19,652.04 ppm), Na (3755.10 ppm), Mg (1763.94 ppm) and Ca (1676.81 ppm) and micro-minerals including Fe (220.89 ppm), Zn (34.87 ppm), Mn (15.82 ppm) and Cu (10.64 ppm). Cordia fruits are also found with phenolic compounds including Gallic acid (4.45 (So(Bg/mg (CD Aq), 3.76 (So(Bg/mg (CD 50%), 3.06 (So(Bg/mg (CD 90%), Caffeic acid (3.14 (So(Bg/mg (CD Aq), 2.59 (So(Bg/mg (CD 50%), 1.39 (So(Bg/mg (CD 90%), Vanillic acid ( 0.15 (So(Bg/mg (CD Aq), 0.02 (So(Bg/mg (CD 50%), 0.20 (So(Bg/mg (CD 90%) and Syringic acid (0.52 (So(Bg/mg (CD Aq), 0.88 (So(Bg/mg (CD 50%), 0.01 (So(Bg/mg (CD 90%). These results suggested the potential role of cordia fruits in our dietary system which not only assist in food security but also provide economic security to the local farmers.s